Expiratory reactance abnormalities in patients with expiratory dynamic airway collapse: a new application of impulse oscillometry. Issue 4 (12th November 2018) - Fielding, David I.; Travers, Justin; Nguyen, Phan; Brown, Michael G.; Hartel, Gunter; Morrison, Stephen
Expiratory dynamic airways collapse (EDAC) is a condition that affects the central airways; it is not well characterised physiologically, with relatively few studies. We sought to characterise impulse oscillometry (IOS) features of EDAC in patients with normal spirometry. Expiratory data were hypothesised to be the most revealing. In addition, we compared IOS findings in chronic obstructive pulmonary disease (COPD) patients with and without EDAC. EDAC was identified at bronchoscopy as 75–100% expiratory closure at the carina or bilateral main bronchi. Four patient groups were compared: controls with no EDAC and normal lung function; lone EDAC with normal lung function; COPD-only patients; and COPD patients with EDAC. 38 patients were studied. Mean IOS data z-scores for EDAC compared to controls showed significantly higher reactance ( X ) values including X at 5 Hz, resonance frequency and area under the reactance curve (AX ). EDAC showed significantly greater expiratory/inspiratory differences in all IOS data compared to controls. Stepwise logistic regression showed that resonant frequency best discriminated between EDAC and normal control, whereas classification and regression tree analysis found AX ≥3.523 to be highly predictive for EDAC in cases with normal lung function (14 out of 15 cases, and none out of eight controls). These data show a new utility of IOS: detecting EDAC in patients with normal lung function. Central airway expiratory dynamic airway collapse can be "silent" on breathing tests, but impulse oscillometry can reveal it http://ow.ly/9oIb30lIOka